Financial Management Literacy at the Takmir and Taklim Assembly of the Nurul Islam Kalangtubung Sudiang Makassar Mosque - Sugianto, Sugianto; Jumriani, Jumriani; Hasriani , Hasriani; Akbardin, Muhammad; Kallabe, Amirah; Resmi, Resmi; Ramadhani, Aisyah; Hasanuddin, Hasanuddin (Pusat Studi Pembangunan dan Pemberdayaan, 2025)
This Community Service activity aims to enhance financial literacy among Takmir (mosque administrators) and Majelis Taklim (Islamic study groups) to improve their financial management skills and accountability within the mosque. As non-profit religious organizations, mosques require proper financial governance to ensure the effective use of funds and foster public trust. The program focuses on addressing three core issues: (1) lack of awareness among mosque administrators and Majelis Taklim regarding the importance of financial accountability to the congregation; (2) limited knowledge of basic accounting principles for preparing financial reports; and (3) insufficient understanding of financial reporting as a key accountability tool. The activity began with a pre-survey to identify specific challenges faced by the target groups. A pre-test was then conducted through interviews to evaluate participants’ initial knowledge of mosque financial management. The main activities included socialization, financial literacy education, Excel-based bookkeeping training, and mentoring. A post-test was also carried out to assess improvements in participants’ understanding. The program was implemented on Saturday, March 19, 2025, from 09:30 to 16:00 WITA at the Nurul Islam Kalantubung Mosque in Sudiang, Makassar City, with 25 mosque administrators and Majelis Taklim members participating. As a result of the training, participants demonstrated enhanced knowledge of financial management, gained the ability to prepare structured financial reports using Excel, and increased transparency and accountability. This led to a boost in public trust toward the mosque's financial governance.